Blurry objectives threaten engagement and profitability: Language of expectations ensures employees know what they are working toward. Issue 2 (9th March 2015) - Purse, Nigel
Abstract : Purpose: – Considers the limitations of traditional objective setting and looks at an alternative approach using a conversation around mutual expectations. Design/methodology/approach: – Explains that a conversational approach requires parties to look at their purpose at work and the expectations of support they have of others at a deeper level. Findings: – Examines deficiencies in traditional performance-management processes, including research about how clear employees are on what they are working toward. Proposes a new approach using the language of purpose and expectations to enhance the objective-setting process. Explains why purpose and expectations are so powerful. Examines why this conversation is so important and why it does not usually happen in a business environment. Practical implications: – Considers that performance management works best when both parties are explicit and honest about their purpose at work and what support they need to achieve this purpose through structured conversation. Social implications: – Advances the view that employees are more engaged when they are working toward a purpose more meaningful than simply receiving a pay check. Originality/value: – Emphasizes that the attraction, development, management and retention of talented people are critical to the success of all organizations.